2021
DOI: 10.1021/acsami.0c22153
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Manufacturing of Amorphous Alloys by a Facile Electrodeposition Approach and Their Property Dependence on the Local Atomic Order

Abstract: Metallic glasses are a unique class of materials combining ultrahigh strength together with plastic-like processing ability. However, the currently used melt quenching route to obtain amorphous alloys has a high cost basis in terms of manufacturing and expensive constituent elements often necessary to achieve the glassy state, thus hindering widespread adoption. In contrast, multimaterial electrodeposition offers a low-cost and versatile alternative to obtain amorphous alloys. Here, we demonstrate multiscale m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 70 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…Thus, higher current densities can result in amorphous coatings. For example, the preparation of Ni 100− x P x ( x = 0, 5, 10, 15, and 25 at%) amorphous coatings [ 227 ] made use of an electrolyte of phosphorous acid (H 3 PO 3 ), nickel sulfate (NiSO 4 •6H 2 O), nickel chloride (NiCl 2 •6H 2 O), boric acid (H 3 BO 3 ), and sodium dodecyl sulfate (NaCl 2 H 25 SO 4 ), a cathode of copper, and an anode of nickel. The electrodeposition process was controlled by varying the peak current densities, using 20 A dm −2 for Ni 95 P 5 , 17 A dm −2 for Ni 90 P 10 , 12 A dm −2 for Ni 85 P 15 , and 5 A dm −2 for Ni 75 P 25 .…”
Section: Manufacturing Approachesmentioning
confidence: 99%
“…Thus, higher current densities can result in amorphous coatings. For example, the preparation of Ni 100− x P x ( x = 0, 5, 10, 15, and 25 at%) amorphous coatings [ 227 ] made use of an electrolyte of phosphorous acid (H 3 PO 3 ), nickel sulfate (NiSO 4 •6H 2 O), nickel chloride (NiCl 2 •6H 2 O), boric acid (H 3 BO 3 ), and sodium dodecyl sulfate (NaCl 2 H 25 SO 4 ), a cathode of copper, and an anode of nickel. The electrodeposition process was controlled by varying the peak current densities, using 20 A dm −2 for Ni 95 P 5 , 17 A dm −2 for Ni 90 P 10 , 12 A dm −2 for Ni 85 P 15 , and 5 A dm −2 for Ni 75 P 25 .…”
Section: Manufacturing Approachesmentioning
confidence: 99%
“…The majority of PGM catalysts studied till date are crystalline, which favor catalytic reactions primarily along few crystallographic orientations, , thereby limiting the full potential of the catalyst. In contrast, bulk metallic glasses (BMGs) represent a new paradigm in electrocatalyst design and have shown promising performance in many catalytic reactions due to their disordered atomic structure and high density of low-coordination surface sites. Each surface site in a metallic glass is potentially active because of atomic-scale disorders and electron localization . Furthermore, BMGs have the unique appeal of facile and scalable thermoplastic manipulation at the nanometer length scale to synthesize complex hierarchical nanostructures that are attractive for catalytic applications. , Noble metal-based BMG catalysts, such as PdNiCuP, PdNiPB, PtCuNiP, PdCuNiP, and PtPdCuNiP, have shown significantly higher activity compared to pure noble metals.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we bridge the processing-structure-property gap by analyzing SRO and MRO for as-cast, relaxed, and rejuvenated Ni 80 P 20 metallic glass as a model amorphous alloy system. The Ni–P system was chosen because of its simple chemistry and application in a wide range of areas including automotive industries, surface protection from corrosion and wear, and micro/nanoelectromechanical systems (MEMS/NEMS) . Adopting a refined and rigorous classification of structural statistics proposed by Sheng et al, we identified the coordination polyhedra for all the atoms in the model and classified them into two groups: (i) loose packing and (ii) dense packing.…”
Section: Introductionmentioning
confidence: 99%